2020
DOI: 10.1111/aos.14501
|View full text |Cite
|
Sign up to set email alerts
|

Increase in treatment of retinopathy of prematurity in the Netherlands from 2010 to 2017

Abstract: Purpose Compare patients treated for Retinopathy of Prematurity (ROP) in two consecutive periods. Methods Retrospective inventory of anonymized neonatal and ophthalmological data of all patients treated for ROP from 2010 to 2017 in the Netherlands, subdivided in period (P)1: 1‐1‐2010 to 31‐3‐2013 and P2: 1‐4‐2013 to 31‐12‐2016. Treatment characteristics, adherence to early treatment for ROP (ETROP) criteria, outcome of treatment and changes in neonatal parameters and policy of care were compared. Results Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
8
2
Order By: Relevance
“…In this larger cohort around 6% of infants needed laser coagulation for ROP, similar to what is previously reported (5.9%) in a cohort of over 154 000 very preterm infants. Contrary to our results, a recent study in the Netherlands reported an increase in treatment for ROP in the more recent epoch 24. The prevalence was 2.3% in the most recent epoch, however the upper gestational age criterion was higher (ie, 32 weeks) 1.…”
Section: Discussioncontrasting
confidence: 99%
“…In this larger cohort around 6% of infants needed laser coagulation for ROP, similar to what is previously reported (5.9%) in a cohort of over 154 000 very preterm infants. Contrary to our results, a recent study in the Netherlands reported an increase in treatment for ROP in the more recent epoch 24. The prevalence was 2.3% in the most recent epoch, however the upper gestational age criterion was higher (ie, 32 weeks) 1.…”
Section: Discussioncontrasting
confidence: 99%
“…If they would have enrolled, the increase between 2009 and 2017 would have reached statistical significance as in 2009 only 1 patient with sROP could not be coupled ( p = 0.009). The results of another Dutch study, showing a doubling of treatments from 2013–2017 compared to 2010–2013, support this result [8]. Similar increases in sROP have been reported in Sweden, Denmark, and the UK [14-16].…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, following an interim meta-analysis of the NeOProM group of studies, oxygen saturation targets of NICU-admitted neonates were raised in 2014 [7]. Together with residual confounders, these changes increased the risk for ROP, which was confirmed in an inventory on ROP treatment in the Netherlands, revealing a notable increase of ROP treatment [8], from n = 57 between 2010 and 2013 to n = 139 between 2013 and 2016. As it has nearly been a decade since the first NEDROP study, the purpose of this consecutive, NEDROP-2 inventory was to determine the present risk factors associated with ROP.…”
Section: Introductionmentioning
confidence: 98%
“…Based on a nationwide study in the Netherlands, approximately 40 treatments per year are performed (average over the years 2013–2016, both laser and anti-VEGF) ( 3 ). Based on the STOP-ROP study, progression from ROP stage 2 to treatment is 48% when receiving standard saturation targets ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the intended amount of oxygen to prevent ROP in the two pathophysiologic phases is opposite (i.e., hypoxia in the early phase and hyperoxia in the late phase), separate evaluation of therapeutic strategies in each phase is necessary to prevent neutralizing results. Although theoretically these two phases have a gradual overlap around 32 weeks postmenstrual age, pragmatically a distinction between early and late phase is warranted by the fact that oxygen-related late phase interventions are performed in the weeks before ROP treatment, which is on average at 37 weeks postmenstrual age ( 3 ). This short report focusses on late phase oxygen strategies and describes opportunities and difficulties when designing a study on the effect of late phase oxygen strategies in preterm infants to prevent development and treatment for ROP.…”
Section: Introductionmentioning
confidence: 99%